Fully Covered Metallic Stents for the Treatment of Benign Airway Stenosis - Caroline Dahlqvist; Sebahat Ocak; Maximilien Gourdin; Anne Sophie Dincq; Laurie Putz; Jean-Paul d’Odémont (Canadian Respiratory Journal)
Introduction. We herein report our experience with new fully covered self-expanding metallic stents in the setting of inoperable recurrent benign tracheobronchial stenosis. Methods. Between May 2010 and July 2014, 21 Micro-Tech® FC-SEMS (Nanjing Co., Republic of Korea) were placed in our hospital in 16 patients for inoperable, recurrent (after dilatation), and symptomatic benign airway stenosis. Their medical files were retrospectively reviewed in December 2014, with focus on stent’s tolerance and durability data. Results. Twenty-one stents were inserted: 13 for posttransplant left main bronchus anastomotic stricture, seven for postintubation tracheal stenosis, and one for postlobectomy anastomotic stricture. Positioning was easy for all of them. Stents were in place for a mean duration of 282 days. The most common complications were granulation tissue development (35%), migration (30%), and sputum retention (15%). Fifty-five % of the stents (11/20) had to be removed because of various complications, without difficulty for all of them. None of the patients had life-threatening complications. Conclusion. Micro-Tech FC-SEMS were easy to position and to remove. While the rate of complications requiring stent removal was significant, no life-threatening complication occurred. Further studies are needed to better define their efficacy and safety in the treatment of benign airway disease.